Penggunaan Metode Permainan Monopoli Dengan Media Termodifikasi Dalam Meningkatkan Motivasi Dan Hasil Belajar Siswa Pada Pembelajaran Ipa SD Muhammadiyah 18 Surabaya - Nasrul Anam (PEDAGO BIOLOGI, 2017)
Abstract : This study aims to determine 1) Increasing students' motivation towards the usage of monopoly game with modified media on learning science at SD Muhammadiyah 18 Surabaya, 2) Student learning outcomes on the use of monopoly games with modified media of science learning on students of SD Muhammadiyah 18 Surabaya, 3) Students’ responses on monopoly game methods with modified media. The research type was Pre-experimental with One Pretest-Postest group design. The sample of research was students of class V at SD Muhammadiyah 18 Surabaya in the academic year 2015-2016. Data collection techniques used was observation, test and questionnaire. Data analysis techniques used was descriptive quantitative. The data were processed using SPSS version 20 at 0,05 significance. The result of this study obtained from the students' learning outcomes on the use of monopoly game method showed the pre-test average value is 71.67 and the post-test average is 90.42.There is students’ motivation that showed in the group with the success percentage of 82% (very good). The students’ response after learning using monopoly game method is very good with percentage of 97,6%.